Tropical peatland village communities’ self-perceived attitude and behaviour changes regarding fire usage - Acep Akbar; Grahame B. Applegate; Agus Kurniawan; Etik E.W. Hadi; Nafila I. Idrus; Virni Arifanti (Mires and Peat)
Indonesia has the world’s second largest national extent of tropical peat deposits, after Brazil. Forest and land fires cause serious disturbance to these peatlands. Whereas more than two million hectares of peatlands burned during 2015, there was an overall decrease in the incidence of fires between 2016 and 2019. This raises the question of whether the decline was due to a change in the behaviour of human communities with regard to their use of fire. This study investigated self-perceived attitudes and behaviour changes amongst communities living in peatlands. Two villages in each of three districts (Pulang Pisau, Kapuas, OKI) within two provinces (Central Kalimantan, South Sumatra) were included. In-depth semi-structured interviews based on a questionnaire were conducted with 90 respondents (15 people per village). The results showed the perception that nearly all fires were caused by people using fire on small-to-medium pieces of land. Post-2015, social conditions were influenced by the creation of new regulations prohibiting burning, innovations in technology, and developing knowledge of the negative effects of fires on the economy. Thus, communities had been made more aware of the importance of preventing fires. This led to reduced interest in burning land and a willingness to start applying modern technology to the preparation of land for various uses. Most community members had actively participated in fire prevention activities. People felt that community landowners carry the greatest share of responsibility for managing their land. The dominant perception was that the ban on burning, socialised at village level, was one of the main reasons for the reduced incidence of fires. The existence of village fire control teams (MPAs), which provide fire-fighting equipment and knowledge, was perceived to strongly support changes in community attitudes to reducing fires. We emphasise that this study presents self-perceived changes in community attitudes and behaviour in using fire.